2021
DOI: 10.1093/schbul/sbaa198
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Aspirin vs Placebo in Patients With Schizophrenia: Results of Two Randomized Controlled Trials

Abstract: Two previous randomized controlled trials (RCTs) suggested that adjunctive aspirin is efficacious in treating schizophrenia. We conducted two 16-week double-blind randomized placebo-controlled RCTs of adjunctive 1000 mg aspirin vs placebo in schizophrenia. Study 1 included 200 patients, with Positive and Negative Syndrome Scale (PANSS) total score as the primary outcome. Study 2 included 160 patients with C-reactive protein (CRP) >1 mg/L at baseline; the primary outcome was PANSS-positive score. Dropout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
3
21
1
Order By: Relevance
“…One study showed a significant reduction in total PANSS score and positive PANSS subscale compared with placebo at 12 weeks ( Laan et al, 2010 ); one also showed reduction in negative and general PANSS subscales at 6 weeks ( Attari et al, 2017 ). Two studies (reported in the same paper) did not show any benefit of Aspirin on PANSS by 16 weeks ( Weiser et al, 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…One study showed a significant reduction in total PANSS score and positive PANSS subscale compared with placebo at 12 weeks ( Laan et al, 2010 ); one also showed reduction in negative and general PANSS subscales at 6 weeks ( Attari et al, 2017 ). Two studies (reported in the same paper) did not show any benefit of Aspirin on PANSS by 16 weeks ( Weiser et al, 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…Precision medicine aims to identify target groups based on clinical and/or biological factors, who may benefit from specific treatments. This approach has been successfully used in the past for other psychiatric conditions ( Raison et al, 2013 ; Huet et al, 2021 ; Cussotto et al, 2022 ), but has only rarely been used for outcomes of RCTs with schizophrenia patients: Martinuzzi et al (2019) successfully stratified a large number of first episode psychosis patients using the PANSS score in a clinical trial with amisulpride and Weiser pre-selected patients using a cut-off value of CRP in a trial with aspirin ( Weiser et al, 2021 ). Interestingly, post-hoc associations in the first episode psychosis patients did reveal an association of one cluster with higher levels of inflammatory markers ( Martinuzzi et al, 2019 ), but the study of Weiser and colleagues failed to show a significant effect of aspirin in the pre-selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, results of the OPTIMISE study, the so-far largest trial investigating clinical subtypes, found an association of specific clinical subtypes and inflammation, which were also relevant for clinical outcomes 4 weeks later ( Martinuzzi et al, 2019 ). Recently, the acute phase protein C-Reactive Protein (CRP) has been used as a single, prospective stratification marker for treatment with aspiring in SCZ ( Weiser et al, 2021 ), but failed to find an effect. We are not aware of research using stratification of patients based on their inflammatory gene-expression profile in SSD to predict response to anti-inflammatory treatment trials.…”
Section: Introductionmentioning
confidence: 99%
“…Results from clinical trials investigating effects of adding aspirin to standard antipsychotic treatment in schizophrenia are inconclusive [51,52]. Although some improvements of positive and negative symptoms have been reported, cognitive measures were not included in these studies [51,52]. This suggests the need for future studies investigating cognitive effects of aspirin in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…For the prevention of dementia, evidence is insufficient to fully evaluate the effect of aspirin on cognitive decline and risk of dementia [49,50]. Results from clinical trials investigating effects of adding aspirin to standard antipsychotic treatment in schizophrenia are inconclusive [51,52]. Although some improvements of positive and negative symptoms have been reported, cognitive measures were not included in these studies [51,52].…”
Section: Discussionmentioning
confidence: 99%